2019
DOI: 10.5455/jpma.21107
|View full text |Cite
|
Sign up to set email alerts
|

Inferior vena cava injuries - a clinical review

Abstract: Inferior vena caval (IVC) injuries are uncommon and challenging to treat. Less than 5% of patients with penetrating abdominal trauma and less than 0.5% of patients with blunt abdominal trauma have this injury. Patient can present with intraperitoneal haemorrhage or with a contained retroperitoneal haematoma. Mostly it is associated with other abdominal structures injuries. Most commonly injured segment is infrarenal IVC. Operative strategy is different for each segment of injured vein. Infrahepatic injuries ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
12
0
4
Order By: Relevance
“…Such patients may also suffer from infection and humid gangrene or even die. Studies have shown that the GCS score, intraoperative hemodynamic status, and the presence of free blood in the abdominal cavity are factors that influence the patients' conditions [ 16 ].…”
Section: Complications Prognosis and Mortality Predictors Of Ivc Injuriesmentioning
confidence: 99%
“…Such patients may also suffer from infection and humid gangrene or even die. Studies have shown that the GCS score, intraoperative hemodynamic status, and the presence of free blood in the abdominal cavity are factors that influence the patients' conditions [ 16 ].…”
Section: Complications Prognosis and Mortality Predictors Of Ivc Injuriesmentioning
confidence: 99%
“…Asthma is a common disease with globally high morbidity, mortality, and economic burden. 22 Asthma is a heterogeneous disease associated with many factors, such as infections, tobacco smoke, cold air, allergens, hormones, exercise, obesity, genetic mutations, and eosinophilia. [23][24][25][26] Meanwhile, asthma is also associated with chronic airway inflammation caused by activation of the immune system.…”
Section: Ctrp3 Alleviated Inflammation In Balf Of Ovastimulated Micementioning
confidence: 99%
“…However, the application of such EBCPGs in Pakistan presents a problem, as the landscape of respiratory conditions differs in many aspects. These include but are not limited to epidemiology [ 4 ], genetic variability [ 10 ], healthcare financing and access [ 11 ], triggers and risk factors [ 12 ], socio-cultural influences [ 13 ], disease related awareness [ 14 ]. In addition, there is a lack of specialist pulmonologists in Pakistan, particularly in rural areas.…”
Section: Introductionmentioning
confidence: 99%